Immunoinflammatory processes: Overlapping mechanisms between obesity and eating disorders?. (July 2022) - Breton, E.; Fotso Soh, J.; Booij, L.
Abstract: Obesity and eating disorders are conditions that involve eating behaviors and are sometimes comorbid. Current evidence supports alterations in immunoinflammatory processes in both obesity and eating disorders. A plausible hypothesis is that immunoinflammatory processes may be involved in the pathophysiology of obesity and eating disorders. The aim of this review is to highlight the link between obesity and eating disorders, with a particular focus on immunoinflammatory processes. First, the relation between obesity and eating disorders will be presented, followed by a brief review of the literature on their association with immunoinflammatory processes. Second, developmental factors will be discussed to clarify the link between obesity, eating disorders, and immunoinflammatory processes. Genetic and epigenetic risk factors as well as the potential roles of stress pathways and early life development will be presented. Finally, implications of these findings for future research are discussed. This review highlighted biological and developmental aspects that overlap between obesity and EDs, emphasizing the need for biopsychosocial research approaches to advance current knowledge and practice in these fields. Highlights: Immunoinflammatory processes have been associated withobesity and eating disorders. Developmental, genetic, and epigenetic research supports that immunoinflammatory processes may play a role in both conditions. Interdisciplinary research efforts could improve our understanding of obesity and eating disorders. Combining knowledge from various fields could lead to the development of novel interventions, thereby optimizing treatment.